Predicting parental distress among children newly diagnosed with craniopharyngioma. Issue 10 (22nd June 2018) - Peterson, Rachel K.; Ashford, Jason M.; Scott, Sarah M.; Wang, Fang; Zhang, Hui; Bradley, Julie A.; Merchant, Thomas E.; Conklin, Heather M.
Abstract: Background: Childhood brain tumor diagnoses are stressful for families. Children diagnosed with craniopharyngioma (Cp) present with particularly challenging medical and cognitive problems due to tumor location and associated biophysiologic comorbidities. This study examined parental distress in a sample of families of patients with Cp treated with proton beam therapy to identify factors for targeting psychological intervention. Procedure: Prior to (n = 96) and 1 year after (n = 73) proton therapy, parents of children diagnosed with Cp (9.81 ± 4.42 years at baseline; 49% male) completed a self‐report measure of distress, the Brief Symptom Inventory (BSI). Children completed cognitive assessment measures at baseline; medical variables were extracted from the study database. Results: At baseline, t ‐tests revealed parents reported higher levels of distress than normative expectations on Anxiety, Depression, Global Severity, and Positive Symptom Distress BSI scales ( P  < 0.05). Linear mixed effects models revealed parent report measures of child executive dysfunction and behavioral issues were more predictive of parental distress than patients' cognitive performance or medical status ( P  < 0.05). Models also revealed a significant reduction only in Anxiety over time ( t  = –2.19, P  < 0.05). Extensive hypothalamic involvement at baseline predicted this reduction ( P  < 0.05). Conclusion: Parents experience significant distress before their child begins adjuvant therapy for Cp, though parental distress appears largely unrelated to medical complications and more related to parent perceptions of child cognitive difficulties (vs. child performance). Importantly, this may be explained by a negative parent reporting style among distressed parents. Knowledge of socio‐emotional functioning in parents related to patient characteristics is important for optimization of psychological intervention.